Measurement of the melting temperature of ZrB2 as determined by laser heating and spectrometric analysis. Issue 6 (1st February 2021) - Stanfield, Austin D.; Manara, Dario; Robba, Davide; Hilmas, Gregory E.; Fahrenholtz, William G.
Abstract: The melting temperatures of two different ZrB2 ceramics were studied using laser induced melting. ZrB2 having a low Hf content, produced by reaction hot pressing, had a melting temperature of 3546 K and a commercial grade ZrB2 had a melting temperature of 3553 K. Uncertainty of the temperature measurements was 1% of the absolute temperature, or ~35 K for both materials based upon 2‐sigma and a 95% confidence interval. While these values were consistent with the previously reported ZrB2 melting temperature of 3518 K, this study was able to measure T m with less uncertainty than previous studies (±45 K). Furthermore, this study assessed the effect of Hf content on melting temperature, finding that melting temperature did not change significantly for hafnium contents of 1.75 to 0.01 at%. This study also measured a normal spectral emissivity of 0.34 for ZrB2 at 3000 K. The emissivity decreased to 0.28 at the melting temperature, then, stabilized at 0.30 in a liquid phase.